Health education by nurses: self-care of patients with chemotherapy from a specialized cáncer Institute in Lima -Perú - Orihuela-Castro, Alda-Eliana (2020)
Objective: To determine self-care in patients with chemotherapy in a pre-post educational intervention test performed by nurses from a specialized oncology institute. Methodology: Quantitative, quasi-experimental, longitudinal. Population of 90 patients with chemotherapy treatment, who were given 3 educational sessions with a pre and post test evaluation; in addition, a questionnaire with 4 dimensions was applied: nutrition, hygiene, infection prevention and avoidance of complications, with 20 items, a Likert scale validated by experts and a reliability of 0.8. Results: In the pre-test, self-care levels were 60% low, 22.2% high and 17.8% medium. In the post-test, self-care levels were 96.7% high and 3.3% medium. In relation to the dimensions of self-care in the pre-test, levels were found to be in Food: 52.2% low and 26.7% high; Hygiene: 42.2% low and 17.8% high; Infection prevention: 36% high and 30% low; and avoidance of complications: 55.6% low and 8.9% high. Finally, in the post-test, levels of: Feeding 94.4% high and 5.6% medium; Prevention of infections: 91.1% high and 8.9% medium. Dimensions: Hygiene and avoidance of complications, obtained 100% high level. Conclusion: It was demonstrated that nurses who promote education on self-care and incorporate the delivery of educational materials, increase knowledge and practices of self-care in their daily lives, which favor the welfare and ensure a quality of life in the patient.